(untitled) - Carlson, Neil R. (Boston, 2017)
Physiology of behavior provides a scholarly yet accessible portrait of the dynamic interaction between biology and behavior. Lead author Neil Carlson and new co-author Melissa Birkett drew upon their experience teaching and working with students to create the new edition of this comprehensive and accessible guide for students of behavioral neuroscience.
Keywords: Tâm sinh lý,Psychophysiology